FORMULAE: Profit and Loss
Profit and Loss
- Cost price = price at which the item is made
- Selling price = price at which item is sold.
- Gain = If SP > CP then SP - CP.
- Loss = If CP > SP then CP - SP.
- Percentage profit = ( Profit * 100) / CP
- Percentage loss = ( Loss * 100) / CP
- SP = ( 100 + Gain% ) * CP / 100
- SP = ( 100 - Loss% ) * CP / 100
- CP = 100 * SP / ( 100 + Gain% )
- CP = 100 * SP / ( 100 - Loss% )
Calculating the percentage profit on basis of amount
Suppose a trader recovers cost of 25 clothes by selling 20
clothes then the percentage profit?
%profit = ( Goods left / Goods sold ) * 100 = ( 5 / 20 ) *
100 = 25%
Calculating %loss when two items are sold at
same value of profit and loss respectively:
Suppose I sell two items, one at profit of 10% and other at
loss of 10% then I shall always have a loss of [ x / 10 ]2
% = ( 10 / 10 )2 = 1% loss
If the price of a commodity increases by R%, then the
reduction in consumption so as not to increase the
New consumption = [R / ( 100 + R )) * 100] %
If the price of the commodity decreases by R%,then the
increase in consumption so as to decrease the expenditure
New expenditure = [ ( R / ( 100 - R ) * 100] %
Results on Population : Let the population of
the town be P now and suppose it increases at the rate
R% per annum, then
Population after n years = P * [1+(R/100)]^n
Population n years ago = P / [1+(R/100)]^n
Results on Depreciation : Let the
present value of a machine be P. Suppose it
depreciates at the rate
R% per annum.
Value of the machine after n years = P * [1-(R/100)]^n
Value of the machine n years ago = P / [1-(R/100)]^n
When A and B are partners and both invest in a ratio say
x:y but at the same time then their ratio of profits sharing
is same as their investment ratio i.e. x:y.
However if A invests 'x' amount for 'p' months and B
invests 'y' amount for 'q' months then their share in
A's share : B's share = x * p : y * q
Laws of Indices:
(i) aᵐ ∙ aⁿ = aᵐ + ⁿ
(ii) aᵐ/aⁿ = aᵐ - ⁿ
(iii) (aᵐ)ⁿ = aᵐ * ⁿ
(v) a-ⁿ = 1/aⁿ
(vi) ⁿ√aᵐ = aᵐ/ⁿ
(vii) (ab)ᵐ = aᵐ ∙ bⁿ.
(viii) (a/b)ᵐ = aᵐ/bm
if A∩B = not empty then n(A-B) + n(B-A) +
= n(A) + n(B) - n(A∩B) and
- n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) -n(A∩C)